Nd:YAG laser‐assisted transendoscopic procedure for treatment of otitis media in a horse. (14th July 2015) - Uhlendorf, F.; Hellige, M.; Cavalleri, J. V. M.; Feige, K.; Ohnesorge, B.
Summary: An 8‐year‐old Warmblood gelding was referred for evaluation of headshaking to the Clinic for Horses, University of Veterinary Medicine Hannover. Based on clinical signs and computed tomography – as well as magnetic resonance imaging – findings, otitis media was diagnosed. Medical treatment including trimethoprim potentiated sulfadimethoxine and meloxicam for 3 weeks did not result in cessation of clinical signs. Therefore, the tympanic cavity was opened transendoscopically using an Nd:YAG‐laser via the guttural pouch according to surgical procedures in human and small animal medicine, leading to a considerable improvement of clinical signs.